Pendidikan Karakter dari Sejarah Peradaban Islam - Pane, Ismail (Journal of Education and Culture, 2023)
The purpose of this study is to evaluate how the picture of the history of Islamic civilization on character education in the real life of mankind. The study method uses literature review of the history of Islamic Civilization. The history books of Islamic civilization are analyzed in depth through an accurate and objective editing process. The next step is to record the existing sources of information for the editing process of journals, books, and other manuscripts related to the history of Islamic civilization and a series of events that contain character education. The findings of this study indicate that the character education brought since Islamic civilization is reinforced by the formulation of the previous Islamic education leaders where moral education is the goal of achieving the formation of good character in every action and behavior of humans, teachers, and learning or students in their lives. true human life, with glorifying character. the values of the character and attributes of Allah SWT are shown through the example of His Prophets. The history of Islamic civilization is the result of the triumph of Islam itself where noble character appears in every triumph of Islam, of course this plays an important role in the progress of Islam from good to bad intelligence can be measured by religion, truth, in terms of culture, social culture, education, use of language, habits of social life, various disciplines and politics.